Analysis of planning, implementation, and evaluation of corporate social responsibility programs in Batam manufacturing companies - Zuliarni, Sri; S, Lidya Elizabeth; Sari, Desi Ratna (Social Sciences Insights Journal, 2025)
Economic actors are obliged to give their company responsibilities to the environment and society. Corporate Social Responsibility (CSR) is an important concept that needs to be developed and integrated by business actors. The realization of CSR itself is what the company does. The program that is designed must also have a good impact on the environment or the community itself. This is what makes the planning, implementation and evaluation of the program important. Good governance will produce good programs and of course will have a good impact and benefits. In this study, it aims to discuss starting from the planning, implementation and evaluation stages of the Blood Donation program carried out at PT. XYZ with the approach method of descriptive qualitative analysis. The results of the research at the planning stage are that PT. XYZ's CSR must ensure and determine the program master first and must be in accordance with the policies held. At the implementation stage, the activities run according to the plan and the problems that arise can be solved. Finally, at the evaluation stage, respondents who filled out the questionnaire admitted that they were satisfied with the activities that had taken place.